Mid-infrared bipolar and unipolar linear polarization detections in Nb₂ GeTe₄ /MoS₂ heterostructures - Han, Jiayue (2024)
Detecting and distinguishing light polarization states, one of the most basic elements of optical fields, have significant importance in both scientific studies and industry applications. Artificially fabricated structures, e.g., metasurfaces with anisotropic absorptions, have shown the capabilities of detecting polarization light and controlling. However, their operations mainly rely on resonant absorptions based on structural designs that are usually narrow bands. Here, a mid-infrared (MIR) broadband polarization photodetector with high PRs and wavelength-dependent polarities using a 2D anisotropic/isotropic Nb2 GeTe4 /MoS2 van der Waals (vdWs) heterostructure is demonstrated. It is shown that the photodetector exhibits high PRs of 48 and 34 at 4.6  and 11.0 µm wavelengths, respectively, and even a negative PR of -3.38 for 3.7 µm under the zero bias condition at room temperature. Such interesting results can be attributed to the superimposed effects of a photovoltaic (PV) mechanism in the Nb2 GeTe4 /MoS2 hetero-junction region and a bolometric mechanism in the MoS2 layer. Furthermore, the photodetector demonstrates its effectiveness in bipolar and unipolar polarization encoding communications and polarization imaging enabled by its unique and high PRs.